Evaluation of Bone Wax Coated Bipolar Coagulation Forceps: Performance and Safety Assessment - Shi, Jichun; Wei, Wei; Wang, Zhen; Ren, Haobin; Jia, Chenguang; Dong, Lixin; Li, Zhengwei; Zhang, Jianjian; Feng, Yu; Huang, Kaixin; Li, Xiang; Chen, Jincao (Frontiers in Surgery, 2022)
Background: Improving the performance of bipolar coagulation forceps is crucial for safer and more accurate neurosurgery. In our department, we found that bone wax (BW) melted by thermal effect of bipolar electrocoagulation can achieve more efficient hemostasis and reduce the amount of BW in neurosurgical procedures associated with bleeding from emissary and diploic veins. Nevertheless, there are still lacking relevant studies to verify our finding. Objective: The study objectives were to evaluate the performance and safety in electrocoagulation: (1) compare the performance of BW coated bipolar coagulation forceps and the conventional anti-stick forceps in vivo, and (2) assess the safety of electrocoagulation with BW coated bipolar coagulation forceps in rat primary motor cortex. Methods: Tissue adhesion was evaluated by comparing the wetting tension and the amount of protein adhered to the forceps tips after electrocoagulation. Thermal damage was assessed by analyzing the thermography and H＆E staining of coagulated rat brain tissues. The hemostatic efficiency was reflected by the number of electrocoagulation until complete hemostasis and the condition of damaged common carotid arteries. The safety of BW coated forceps in electrocoagulation was assessed by evaluating the inflammation of coagulated rat primary motor cortex and the motor functions at the 7th day postoperatively. Results: BW coated forceps had a significantly higher contact angle and adhered less coagulum. Thermography was acquired at 3 seconds, 6 Watts units in rat primary motor cortex in vivo. The highest temperature recorded during BW coated tips application was significantly lower than the uncoated. And there was a relatively smaller tissue injury area produced by the BW coated forceps. Additionally, BW coated forceps improved hemostatic efficiency and caused fewer injuries on the damaged arteries (3 seconds, 10 Watts units). More importantly, electrocoagulation with BW coated forceps led to no significant motor function impairments and less glial and microglia responses. Conclusion: This study reveals that BW coated bipolar coagulation forceps can provide a convenient, cost-efficient, safer and more efficient way for hemostasis. More researches are needed to evaluate the electrocoagulation with BW in the long term and verified our finding in human beings.